Catholic and Faith-Based Schools in Africa : Introduction to the Special Issue - Grace, Gerald; Wodon, Quentin (Taylor and Francis, 2022)
Africa is the region of the world where Catholic and other faith-based schools have the largest footprint. One in nine students in a primary school in Africa is enrolled in a Catholic school, and students from the region account for more than half of all students in Catholic primary schools globally. Through the role it plays in Africa, the Catholic Church is at the forefront of providing educational opportunities in low-income countries, but challenges abound. In particular, learning poverty defined as the inability of 10-year-old children to read and understand an age-appropriate text, affects nine in ten children in sub-Saharan Africa. Students in Catholic schools are not immune to this crisis. This article introduces a framework from the World Bank on how we could end the learning crisis and summarizes the contributions of the articles included in this issue in terms of that framework.